2005
DOI: 10.1681/asn.2004121034
|View full text |Cite
|
Sign up to set email alerts
|

Familial Vesicoureteral Reflux: Testing Replication of Linkage in Seven New Multigenerational Kindreds

Abstract: Vesicoureteral reflux (VUR) (OMIM %193000), a common cause of childhood renal failure, is strongly influenced by hereditary factors. Familial VUR most closely conforms to autosomal-dominant inheritance, but because of variable penetrance and expressivity, large multigenerational pedigrees tractable to linkage analysis have been difficult to ascertain. A single genome-wide study of familial VUR has demonstrated linkage to chromosome 1p13, with 78% locus heterogeneity. Previous studies in humans have also sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 31 publications
2
54
0
2
Order By: Relevance
“…Three linkage studies, however, have been unable to support these findings. One study on Italian and American kinships with VUR, one on four Dutch families with VUR, and one on UK and Slovenian data sets with VUR found no linkage to the locus of ROBO2 (6,8,11). In this study, syndromic cases of VUR were excluded, and the cases of primary nonsyndromic VUR accompanied by RHD were studied separately.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Three linkage studies, however, have been unable to support these findings. One study on Italian and American kinships with VUR, one on four Dutch families with VUR, and one on UK and Slovenian data sets with VUR found no linkage to the locus of ROBO2 (6,8,11). In this study, syndromic cases of VUR were excluded, and the cases of primary nonsyndromic VUR accompanied by RHD were studied separately.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have identified variants of the roundabout, axon guidance receptor, homolog 2 (ROBO2) gene in patients with VUR and VUR accompanied by other CAKUT, but their conclusions are contradictory on whether or not mutations of the ROBO2 gene are a causative factor of VUR or VUR-other CAKUT (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…24,105,106 roBo2/sliT2 to date, two groups have reported ROBO2 gene missense mutations associated with vur, 107,108 and a further study has supported the hypothesis that variations in ROBO2 and SLIT2 are rare causes of vur in humans. 109 However, subsequent candidate gene linkage studies including the ROBO2 locus found no evidence for linkage, 23 and similar study has found no evidence of linkage at SLIT2. 24 …”
Section: Human Genetic Studiesmentioning
confidence: 96%
“…two attempts to replicate their findings were unsuccessful. 23,24 this may be explained by the fact that the map positions of some of the markers linked to vur by Feather et al 22 have since been revised-the marker defining one side of their reviews…”
Section: Genome-wide Scansmentioning
confidence: 99%
See 1 more Smart Citation